Stable Isotopic Stratification and Growth Patterns of Ground Ice in Permafrost on the Qinghai‐Tibet Plateau, China. (24th May 2016) - Wu, Yuzhong Yang, Qingbai; Jiang, Guanli; Zhang, Peng
Abstract: Stable isotope analysis of ground ice from a deep borehole in permafrost in the Kunlun Mountain Pass on the Qinghai‐Tibet Plateau, China, was carried out to assess the water source and origin of the ground ice. Five sections were isotopically distinguished in the borehole. The ground‐ice samples had δ 18 O values ranging from −20.2 to −8.5‰ (mean: −11.0‰), δD values from −151.9 to −73.1‰ (mean: −84.9‰) and D‐excess values from −16.7 to 9.8‰ (mean: 2.7‰). The isotopic contents and the freezing line (Sδ   18  O‐δD = 6.86) of ground‐ice samples in the five sections showed significant deviations from modern isotopic values of regional precipitation and surface water, indicating discrepancies in the replenishment of source water and different climatic conditions during periods of ice formation. Near‐surface ground ice (0–3 m depth) (D‐excess: 9.8‰) formed mainly from modern precipitation, whereas deep ground ice was related to the source water and freezing conditions during ice formation. Ground ice from 3.8 to 9.6 m and from 9.6 to 16 m is segregated in origin and a stable freezing front at 9.6 m was identified. Ground ice from 16 to 50 m was replenished by precipitation in the period during ground‐ice formation. Between 50 and 91.3 m, ground ice formed in an unstable climate and a palaeo‐permafrost table at 91.3m was distinguished. Copyright © 2016 John Wiley & Sons, Ltd.